The Socialization of Tax as a Moderation Variable Towards the Taxpayer Compliance of Industrial Performer in Kudus Regency - Pitaloka, Lola Kurnia; Kardoyo, Kardoyo; Rusdarti, Rusdarti (Universitas Negeri Semarang, 2018)
The objectives of this study are to analyze the effect of understanding tax rules and awareness of taxpayer compliance as well as analyze the influence of understanding tax rules and awareness of taxpayer compliance after it is moderated by tax socialization. This study was quantitative research and used deductive approach as well as causal studies. The location in this study was in Kudus Regency and the population was a medium and large industry performer, they were 174 industry performers. The determination of the sample in this study was by using saturated sampling or census method which means the number of samples equal to the number of population. This study used regression analysis for the moderation variables. The results of this study is the understanding of tax and awareness have a positive and significant effect on taxpayer compliance. The tax socialization affects and strengthens the relationship between understanding tax rules on taxpayer compliance but fails to affect the relationship between taxpayer awareness and compliance. In this study, tax socialization runs two types of moderation: pseudo-moderation and moderation of predictors. Hasil dalam penelitian ini adalah pemahaman peraturan pajak dan kesadaran berpengaruh positif dan signifikan terhadap kepatuhan wajib pajak. Sosialisasi pajak mempengaruhi dan memperkuat hubungan antara pemahaman peraturan pajak terhadap kepatuhan wajib pajak namun gagal mempengaruhi hubungan antara kesadaran dan kepatuhan wajib pajak. Dalam penelitian ini, sosialisasi pajak menjalankan dua jenis moderasi yaitu moderasi semu dan moderasi prediktor. The objectives of this study are to analyze the effect of understanding tax rules and awareness of taxpayer compliance as well as analyze the influence of understanding tax rules and awareness of taxpayer compliance after it is moderated by tax socialization. This study was quantitative research and used deductive approach as well as causal studies. The location in this study was in Kudus Regency and the population was a medium and large industry performer, they were 174 industry performers. The determination of the sample in this study was by using saturated sampling or census method which means the number of samples equal to the number of population. This study used regression analysis for the moderation variables. The results of this study is the understanding of tax and awareness have a positive and significant effect on taxpayer compliance. The tax socialization affects and strengthens the relationship between understanding tax rules on taxpayer compliance but fails to affect the relationship between taxpayer awareness and compliance. In this study, tax socialization runs two types of moderation: pseudo-moderation and moderation of predictors.